2018
DOI: 10.5371/hp.2018.30.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cam Deformity with Associated Femoroacetabular Impingement Syndrome in Hip Joint Computed Tomography of Asymptomatic Adults

Abstract: PurposeFemoroacetabular impingement (FAI) is considered an important cause of early degenerative arthritis development. Although three-dimensional (3D) imaging such as computed tomography (CT) and magnetic resonance imaging are considered precise imaging modalities for 3D morphology of FAI, they are associated with several limitations when used in out-patient clinics. The paucity of FAI morphologic data in Koreans makes it difficult to select the most effective radiographical method when screening for general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…16 However, that study did not perform subgroup analysis by age or sex. 6,16,29 Previous studies have suggested that the cam variant is an acquired phenomenon, particularly in men during the second growth spurt, and that it is highly influenced by exercise-related loads applied to the hip during this phase. 55 The 3 radiographic signs of cam-type FAI demonstrated a constant prevalence across age and sex, resulting in no significant differences in sex.…”
Section: Cam-type Variantmentioning
confidence: 96%
“…16 However, that study did not perform subgroup analysis by age or sex. 6,16,29 Previous studies have suggested that the cam variant is an acquired phenomenon, particularly in men during the second growth spurt, and that it is highly influenced by exercise-related loads applied to the hip during this phase. 55 The 3 radiographic signs of cam-type FAI demonstrated a constant prevalence across age and sex, resulting in no significant differences in sex.…”
Section: Cam-type Variantmentioning
confidence: 96%
“…This is caused by repetitive impact of the proximal portion of the femoral neck against the acetabular labrum and its adjacent cartilage. 54 Two types of femoroacetabular impingement can be distinguished the cam and pincer one. 54 These two types of FAI can occur as separate entities, but it has recently been shown that combined impingement occurs in the majority of cases (86%).…”
Section: Femoroacetabular Impingement and Cam Deformitymentioning
confidence: 99%
“…54 Two types of femoroacetabular impingement can be distinguished the cam and pincer one. 54 These two types of FAI can occur as separate entities, but it has recently been shown that combined impingement occurs in the majority of cases (86%). 54 In case the chondral injury results from cam-type impingement, this is more severe than those which result from pincer type.…”
Section: Femoroacetabular Impingement and Cam Deformitymentioning
confidence: 99%
See 2 more Smart Citations